Ouvidorias públicas e canais de participação cidadã: análise da contribuição das Tecnologias de Informação e Comunicação (TICs) para os meios de interlocução disponibilizados à população - Rodrigues, Mariana da Silva (2018)
The progress in Information and Communication Technologies (ICTs) favors new ways of relating between citizens and governments. In this scenario, the public ombudsmen are pointed by the Brazilian Government as an instrument to enable this interaction and over the years have been improving to facilitate the channels of access of the population to these entities. Therefore, the objective of this study is to analyze the performance of the public ombudsman of federal higher education institutions (IFES) in the citizen participation, in order to identify if these entities are prepared to listen to the population and how they organize themselves in this sense. The proposed methodology has a quali-quantitative nature, starts from a theoretical review of the central themes of the study, documentary survey and application of a questionnaire addressed to the public ombudsman of the IFES at the national level. It was also adopted a multiple case study in three ombudsman of IFES, with simulation of attendance of the manifestations by channel and interviews with the responsible ombudsmen. The results of the study show that IFES public ombudsman, despite presenting some similarities of processes and guidelines, still need norms that standardize the rules of action, as well as oversight of what already exists in this sense, in order to ensure similar conditions of attendance and encouragement of participation. In addition, the data revealed that ICTs amplify the access of citizens who wish to interact with the State through the public ombudsman, but in order for these entities to effectively provide space for citizen participation, it is still necessary to invest in the structure, standards and dissemination of the role of public ombudsman by the public authority. With this, it is expected to stimulate the construction of a culture of more proactive participation and to arouse in the population interest to cooperate with the public administration.